1960
DOI: 10.1139/b60-068
|View full text |Cite
|
Sign up to set email alerts
|

SYNERGISM BETWEEN PRATYLENCHUS PENETRANS (COBB) AND VERTICILLIUM ALBO-ATRUM R. & B. IN EGGPLANT WILT

Abstract: Studies conducted in steam-sterilized soil inoculated with Verticillium alboatrum and Pratylenchus penetrans demonstrated a synergistic relationship between fungus and nematode. At low and intermediate levels of Verticillium inoculum, the nematode increased wilt and the increase may be a function of the number of nematodes present. Except at the high inoculum levels of Verticillium, significantly larger numbers of P. penetrans occurred in eggplant roots in the presence than in the absence of the fungus. The ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

1969
1969
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 3 publications
1
10
0
Order By: Relevance
“…An increase in the final density of Pratylenchus spp. on different hosts (MCKEEN and MOUNTAIN 1960, MICHELL and POWELL 1972, MOUNTAIN and MCKEEN 1962 and of root-knot nematode on chrysanthemum (JOHNSON and LlTTRELL 1969) infected with vascular wilt fungi have been reported, increase in numbers of Pratylenchus coffeae on chrysanthemum infected with R. solani was also recorded in the present studies but it was found to be reduced in presence of P. aphanidermatum (Table 1). P. aphanidermatum is reported to suppress rootknot nematode on chrysanthemum (JOHNSON and LITTRELL 1970), BURPEE and BLOOM (1978) observed suppression in the population of Pratylenchus penetram on potato infected with Verticillium wilt fungus.…”
Section: Discussionsupporting
confidence: 76%
“…An increase in the final density of Pratylenchus spp. on different hosts (MCKEEN and MOUNTAIN 1960, MICHELL and POWELL 1972, MOUNTAIN and MCKEEN 1962 and of root-knot nematode on chrysanthemum (JOHNSON and LlTTRELL 1969) infected with vascular wilt fungi have been reported, increase in numbers of Pratylenchus coffeae on chrysanthemum infected with R. solani was also recorded in the present studies but it was found to be reduced in presence of P. aphanidermatum (Table 1). P. aphanidermatum is reported to suppress rootknot nematode on chrysanthemum (JOHNSON and LITTRELL 1970), BURPEE and BLOOM (1978) observed suppression in the population of Pratylenchus penetram on potato infected with Verticillium wilt fungus.…”
Section: Discussionsupporting
confidence: 76%
“…Sam ples of lower parts of stems of wilted plants were plated on moist filter paper (McKeen & Thorpe 1971 ) to determine the Vertkillium species present. During late August, after the tops had matured, the plots were harvested and the yields of tubers were determined by weight.…”
Section: Wilt Development and Yield Determinationmentioning
confidence: 99%
“…have been associated with a disease of tobacco called brown root rot (Jenkins 1944;Koch and Stover 1950;Mountain 1954). Also P. penetrans has been shown to increase the incidence of Verticillium wilt in eggplants if the level of Verticillium albo-atrum R. & B. in the soil is low (McKeen and Mountain 1960). Similarly, Pratylenchus spp.…”
Section: The Association Of Rootlesion Nematodes With Reduced Growthmentioning
confidence: 99%